2021
DOI: 10.1155/2021/6139308
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effects of Protocatechuic Acid and Protocatechuic Aldehyde: Old Wine in a New Bottle

Abstract: Phenolic compounds are naturally present as secondary metabolites in plant-based sources such as fruits, vegetables, and spices. They have received considerable attention for their antioxidant, anti-inflammatory, and anti-carcinogenic properties for protection against many chronic disorders such as neurodegenerative diseases, diabetes, cardiovascular diseases, and cancer. They are categorized into various groups based on their chemical structure and include phenolic acids, flavonoids, curcumins, tannins, and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 189 publications
(195 reference statements)
0
45
1
1
Order By: Relevance
“…PCA has also been compared to its precursor molecule, protocatechuic aldehyde (PLA)—the parent anthocyanin compound from which PCA is directly generated [18] , [19] . Findings not only demonstrate the antioxidant, anti-cell death, and other pharmacological properties of PCA in rats but these properties of PCA, when compared with those of PLA, were also found to be significantly higher [18] , [19] . Interestingly, the pharmacological properties of PCA, including its metal-chelating properties, show that these DIC events are negatively regulated by PCA [19] .…”
Section: Introductionmentioning
confidence: 99%
“…PCA has also been compared to its precursor molecule, protocatechuic aldehyde (PLA)—the parent anthocyanin compound from which PCA is directly generated [18] , [19] . Findings not only demonstrate the antioxidant, anti-cell death, and other pharmacological properties of PCA in rats but these properties of PCA, when compared with those of PLA, were also found to be significantly higher [18] , [19] . Interestingly, the pharmacological properties of PCA, including its metal-chelating properties, show that these DIC events are negatively regulated by PCA [19] .…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant assessments of purslane seed extracts revealed that MOH‐extract is more effective as radical‐scavenger, whether in hydrogen atom transfer (HAT) assays like ORAC, or in electron transfer (ET)‐based assays including DPPH, ABST, FRAP and metal chelation. This is not surprising considering the higher content of phenolic compounds that was confirmed by HPLC quantification results, identifying 19 peaks of different phenolic/polyphenolic and flavonoid compounds, particularly protocatechuic acid, a major metabolite of anthocyanins found in green tea and known as potent radical quencher (Zhang et al, 2021). However, the starking result was that the fixed oil extract showed a remarkable reducing capacity of phosphomolybdate, with the minimum IC50 value recorded (50.82 ± 3.4 μg/ml) compared with MOH‐extract that showed a weak reducing capacity with a very high IC50 value (1866 ± 73.8 μg/ml) despite its superior radical‐scavenging power pronounced in other assays, and even to ascorbic acid (134.42 ± 13.4 μg/ml).…”
Section: Discussionmentioning
confidence: 77%
“…In addition, Zhang et al . (2021a, 2021b) detected six anthocyanins and their contents in blueberry by HPLC triple quadrupole mass spectrometry. In the positive ion mode, the scanning range was ( m / z ): 100–600.…”
Section: Determination Of Anthocyanin Contentmentioning
confidence: 99%
“…This shows that anthocyanins are more stable at low temperature. However, it is worth noting that, although high temperatures degrade anthocyanins and reduce their content, the degradation products are procatechin and catechin, which still have antioxidant effects (Zhang et al, 2021a(Zhang et al, , 2021b. Therefore, high temperatures cannot significantly affect its antioxidant properties.…”
Section: Stabilitymentioning
confidence: 99%